DESIGNING A MARKETING MIX STRATEGY MODEL TO INCREASE SALES OF PITMEY SWEET PRODUCTS - Evita Mei Kusumaningrum; Wirawan Endro Dwi Radianto (International Journal of Economic Integration and Regional Competitiveness, 2024)
Objective: This study aims to design a marketing mix strategy model to enhance sales performance at Pitmey Sweet, a food and beverage business specializing in pastries and bread in Surabaya. Method: The research employs a qualitative method with a case study approach. Data were collected through documentation, observation, and purposive sampling interviews. The analysis utilizes the 11P marketing mix framework, encompassing product, price, place, promotion, people, physical evidence, process, packaging, programming, partnerships, and promises. Results: The findings indicate that the application of the 11P marketing mix strategy effectively identifies key marketing tools that contribute to increased sales at Pitmey Sweet. Each component of the 11P framework plays a significant role in strengthening the company’s market position and improving consumer satisfaction. Novelty: This study offers a comprehensive integration of the 11P marketing mix model in the context of the pastry and bread industry, providing a strategic reference for similar businesses aiming to enhance sales through innovative and consumer-centric marketing approaches.